As políticas educacionais para o espaço agrário na mesorregião oeste do Paraná (1950-2014) - Bem, Anderson (2016)
It is common in the academic literature the crisis scenario of the Rural Education. From the point of view of eradication of Rural School in process, the crisis of rural education is an incontestable fact. However, public investment focused on Rural Education in Brazil, throughout history, demonstrates two educational policies: one for large farm and one for the smallholding. To study the directed education policy for the Agrarian Space in West Mesoregion of Paraná, we identified two phases of educational policy. In the first place the construction of Rural Schools was intense between 1950-1970, and guided in the colonization of land-based small farm system. This phase ended with soil mechanization and the consequent exodus started in the late 1970s and intensified during the 1980s. In the second place the expansion of higher and technical courses targeted for Agribusiness - educational policy that becomes clear already in the 1990s. With the development of agribusiness in West Mesoregion of Paraná, there was the creation and expansion of a public infrastructure of technical and higher education maintained by the federal and state level institutions. The municipalities of Medianeira, Palotina and Marechal Cândido Rondon are those where there is more clearly the relationship between the development of agribusiness in local / regional and educational policy. The very spatial formation of the municipalities is intertwined with the history of the companies in the agribusiness sector. The educational policy directed to the agrarian space in West Mesoregion of Paraná in recent decades sought to meet the demands of regional development based on agribusiness, model sustained by food export. This fact is evidenced by the emergence of higher-level courses and technical, located near the food industry, especially of the meat and dairy and close relationship with the productive sector. Already the educational policy for the social segment of the smallholding is the school transport